Common defect on IBS educational building / Ahmad Danial Mohammed Nor - Mohammed Nor, Ahmad Danial (Faculty of Architecture, Planning and Surveying, 2010)
The construction industry plays a major role in Malaysian economic growth. However, the industry is not without weaknesses. The challenges often occur in the area of productivity, efficiency of work, quality of work and the delivery of work. The intensive use of foreign unskilled workers, low technology equipments and out-of-dated construction methods, have eventually caused low productivity and inefficiency of work at construction site. IBS is one of the improved building Systems that are being introduced in the construction industry, to achieve the target of faster completion with mass production of the building elements in places out of its final location in a building. A study was conducted to analyses common defect on IBS educational building in Malaysia. Its may be starting from design stage till installation stage. In this research also analyze a caused of the defect based on 5-difference educational project around Malaysia. In this research it used three methodologies to gather all the data. It used a questionnaire, interview and observation. Every chapter has its own perceptions regarding IBS. The case studies been carried out to 5 project as SMK Setia Alam (Selangor), SKJ (T) Kajang (Selangor), SK Nyiur Tujoh (Terenganu), SK Rantau Panjang (Terenganu) and UiTM Jengka (Pahang). In this research also shows the most common defect and the most causes of the related defect on every case study. Summaries have been made to solve the entire defect from those most main factors the influence to defect.